Meditation-Relaxation (MR Therapy) for Sleep Paralysis: A Pilot Study in Patients With Narcolepsy - Jalal, Baland; Moruzzi, Ludovico; Zangrandi, Andrea; Filardi, Marco; Franceschini, Christian; Pizza, Fabio; Plazzi, Giuseppe (Frontiers in Neurology, 2020)
Sleep paralysis (SP) is a condition where a person is paralyzed upon waking or falling asleep. SP afflicts approx. 20% of people, and is also one of the typical symptoms in narcolepsy. During SP the sleeper may experience hallucinations. Unsurprisingly, SP is associated with great fear globally. To date, there are no published clinical trials or outcome data for treating this condition. However, few non-pharmacological interventions have been proposed, including cognitive behavioral approaches, and case studies showing clinical amelioration with auto-hypnosis and Meditation-Relaxation (MR) therapy. The latter for instance showed positive preliminary results; when applied for 8 weeks it reduced SP frequency and anxiety/worry symptoms. With this paper we aimed to evaluate, with a small-scale pilot study, the efficacy of MR therapy for SP in patients with narcolepsy. Ten patients with narcolepsy and SP were enrolled in the study. Notably, MR therapy (n = 6), applied for 8 weeks, resulted in a dramatic decrease in the number of days SP occurred (50% reduction); and the total number of SP episodes (54% reduction) in the last month of the study (demonstrated by large within-group effect sizes); unlike the control intervention (deep breathing) (n = 4). These findings are preliminary and exploratory given the small sample. Nonetheless, they represent the first proof of concept at providing empirically-guided insights into the possible efficacy of a novel treatment for frequently occurring SP. Although the study was conducted in patients with narcolepsy we cautiously suggest that the findings may generalize to individuals with isolated SP.